2022
DOI: 10.3390/pathogens11020261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eosinophilic Cationic Protein as a Marker of Alveolar and Cystic Echinococcosis

Abstract: Echinococcosis is a neglected zoonotic disease and a worldwide public health problem caused by infection with the larval stages of taeniid cestodes of the genus Echinococcus. In vitro studies have demonstrated a protoscolecidal effect of eosinophilic cationic protein (ECP), a granule protein of eosinophilic granulocytes, against E. granulosus. Therefore, the main objective of this study was to evaluate ECP as a biomarker in the treatment of alveolar echinococcosis (AE) and cystic echinococcosis (CE). Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Besides suppressing bacteria and viruses, RNase A family members also showed the ability to inhibit parasites in the intestine. Recent studies have revealed that RNase 3 level is significantly increased in patients infected by Ancylostoma duodenale , Necator americanus , Strongyloides stercoralis, or Echinocococcus ( Amoani et al., 2019 ; Hotz et al., 2022 ). Combined the data of RNase 3 in urinary tract infection, RNase 3 may be developed as a general biomarker for parasitic infection.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Besides suppressing bacteria and viruses, RNase A family members also showed the ability to inhibit parasites in the intestine. Recent studies have revealed that RNase 3 level is significantly increased in patients infected by Ancylostoma duodenale , Necator americanus , Strongyloides stercoralis, or Echinocococcus ( Amoani et al., 2019 ; Hotz et al., 2022 ). Combined the data of RNase 3 in urinary tract infection, RNase 3 may be developed as a general biomarker for parasitic infection.…”
Section: Infectious Diseasesmentioning
confidence: 99%